Yr10 gene polymorphism in bread wheat varieties - (:unkn) unknown (ACADEMIC JOURNALS, 2008)
Yellow rust resistance locus Yr10 located on chromosome 1B in Moro and originated from the Turkish line PI178383 was investigated in terms of polymorphism in seven winter type bread wheat cvs. ( Triticum aestivum ssp. Aestivum) Altay2000, izgi2001, Sonmez2001 (yellow rust resistant), Aytin98, ES14, Harmankaya99 ( yellow rust susceptible) and PI178383 as control. Exon 1 (1 - 833 bp) and Exon 2 ( 1989 - 3630 bp) parts of Yr10 were amplified with three primers. Amplification was not observed with E2A primers in Harmankaya99, izgi2001 and Sonmez2001 cvs, while amplification products were observable at all tested varieties with the other primers. PCR results showed that E2A reverse primer is not able to anneal to the three varieties mentioned above. Sequence analysis and bioinformatics analysis proved that there has been single nucleotide changes especially in the second exon. The most similar sequences to the first exon of Harmankaya99, izgi01 and Sonmez2001 are AF509535 (Aegilops tauschii NBS-LRR-like gene), AF509534 (A. tauschii NBS-LRR-like gene sequence) and AF509534, respectively. These results could be helpful in revealing divergence between resistant and susceptible varieties.
Keywords: Triticum aestivum L; yellow rust; resistance gene; PCR; sequence analysis; STRIPE-RUST; YELLOW RUST; DURABLE RESISTANCE; MARKERS; YR5; ALIGNMENT; YR26